Plated steel sheet, member, and method for manufacturing same

By controlling the steel plate composition and heat treatment process, a specific microstructure is formed, which solves the problem of insufficient tensile strength and delayed fracture resistance of high-strength steel plates in the existing technology, and achieves tensile strength of over 1180MPa and excellent plating properties.

CN120882893APending Publication Date: 2025-10-31JFE STEEL CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202480019870.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-28
Filing Date
2024-03-18
Publication Date
2025-10-31

AI Technical Summary

Technical Problem

The tensile strength (TS) of high-strength steel plates in the prior art is less than 1180 MPa, and the characteristics of delayed fracture resistance and plating properties are not considered.

Method used

By controlling the composition of the steel plate and the heat treatment process, martensitic and bainitic structures are formed. Boron is non-uniformly segregated at the original austenite grain boundaries. Combined with cryogenic treatment and secondary annealing, boron is enriched at some grain boundaries to form a specific microstructure to improve the resistance to delayed fracture. At the same time, the boron content is controlled to be above 0.0008% and less than 0.0015%.

Benefits of technology

It achieves a tensile strength (TS) of over 1180 MPa, exhibits excellent resistance to delayed fracture and plating properties, and meets the requirements of high-strength steel plates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

Provided are: a plated steel sheet which has high strength and excellent delayed fracture resistance and plating properties; a member; and a method for producing the plated steel sheet and the member. A plated steel sheet which comprises a steel sheet having a component composition in which C, Si, Mn, P, Al, N, Ti, Nb, and B are specified in mass%, the total area ratio of martensite and bainite being 95.0% or more, the area ratio of retained austenite being 4.8% or less, the area ratio of ferrite being 0.2-3.0%, and the plating layer being formed on at least one surface of the steel sheet. The grain size of the prior austenite (primary gamma) is 10 [mu] m or less, the concentration of B in the primary gamma grain boundary between adjacent martensite is 0.05% by mass or more, and the deviation of the concentration of B in the primary gamma grain boundary between adjacent martensite in the same grain boundary is less than 0.010% by mass. The variation in B concentration in the original gamma grain boundary between martensite and ferrite in the same grain boundary is 0.010% by mass or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to coated steel sheets, components, and methods for manufacturing them. Background Technology

[0002] In addition to strength, automotive steel sheets also require excellent resistance to delayed fracture.

[0003] Patent Document 1 discloses a high-strength steel sheet with excellent workability and a method for manufacturing the same. Patent Document 2 discloses a high-strength cold-rolled steel sheet and a method for manufacturing the same.

[0004] Existing technical documents

[0005] Patent documents

[0006] Patent Document 1: Japanese Patent Application Publication No. 2013-147736

[0007] Patent Document 2: Japanese Patent Application Publication No. 2008-106351 Summary of the Invention

[0008] The problem that the invention aims to solve

[0009] However, for the steel plates described in Patent Documents 1 and 2, the tensile strength TS is less than 1180 MPa, and the delayed fracture resistance characteristics are not considered.

[0010] The present invention was made in view of the above circumstances, and its object is to provide plated steel sheets, components and methods thereof with a tensile strength TS of 1180 MPa or above, which have high strength, resistance to delayed fracture and excellent plating properties.

[0011] It should be noted that, in this invention, high strength refers to a tensile strength TS of 1180 MPa or higher as measured according to JIS Z2241 (2011).

[0012] In addition, excellent resistance to delayed fracture means that when the test piece is subjected to a constant load test with a tensile stress of 1800 MPa on the surface and then immersed in a hydrochloric acid aqueous solution with pH 3 for 100 hours, no cracks are produced.

[0013] In addition, excellent plating performance means that there are no unplated areas when visually inspected.

[0014] Methods for solving problems

[0015] In order to solve the above problems, the inventors have conducted in-depth research and have come to the following conclusions.

[0016] To obtain a tensile strength (TS) of 1180 MPa or higher, martensite or bainite can be used as the main phase. Additionally, to improve resistance to delayed fracture, a content of 0.0015% by mass or higher of boron is effective.

[0017] It is believed that B has the effect of strengthening the grain boundaries that become fracture paths by segregating from the original austenite grain boundaries.

[0018] On the other hand, if boron (B) is added, the oxides of Si and Mn containing B will accumulate on the surface during annealing, reducing the plating properties. It is known that a B content of less than 0.0015% by mass has little effect on plating properties. Therefore, methods to improve resistance to delayed fracture by reducing the B content to less than 0.0015% were investigated. It was then realized that by causing B to segregate unevenly at the original austenite grain boundaries, forming grain boundaries with high and low B concentrations, even with a B content of less than 0.0015%, sufficient B segregation at some grain boundaries can improve resistance to delayed fracture.

[0019] Therefore, a method was investigated to induce non-uniform segregation of boron (B) at the original austenite grain boundaries and increase the B concentration at some grain boundaries. It was found that after two processes of B segregation at the grain boundaries, and with the nucleation of new austenite grains in the second process, non-uniform B segregation occurs. If the cold-rolled sheet is annealed in the austenite region, B segregates at the austenite grain boundaries, but at this point, B diffusion is insufficient, and dissolved B exists, resulting in non-uniform B segregation and inadequate enrichment.

[0020] After temporarily cooling the steel to form martensite and bainite, a second annealing results in a reverse austenite transformation. Regarding this, if residual austenite exists after the first annealing and cooling, it will serve as a nucleus for austenite with the same crystal orientation as that formed during the first annealing. Furthermore, since martensite and bainite contain numerous dislocations, boron dissolved within them diffuses rapidly to the austenite grain boundaries via these dislocations during the second annealing, resulting in uniform boron segregation. However, uniform segregation dilutes the boron concentration at the grain boundaries, necessitating a separation where boron is more concentrated in some grain boundaries and less concentrated in others. Therefore, if deep cryogenic treatment is performed after the first annealing to eliminate some of the residual austenite, a high boron concentration martensite is formed. During the second annealing, a new austenite with a different crystal orientation than the first-formed austenite is nucleated from this martensite. The newly formed austenite grain boundaries are located differently from those of the first-formed austenite grain boundaries, resulting in a dilute and non-uniform boron concentration. The retained austenite from the martensitic transformation during cryogenic treatment is primarily blocky, with film-like retained austenite also remaining after cryogenic treatment. From these thin, film-like retained austenite films, austenite with the same crystal orientation as during the first annealing is formed. If this microstructure is cooled, ferrite forms from the grain boundaries where the boron concentration is low and non-uniform. However, as long as the ferrite area fraction is below 3.0%, a high strength of over 1180 MPa can be ensured. Even with a boron content of less than 0.0015%, the resulting microstructure has boron enriched at the original austenite grain boundaries flanked by martensite, improving resistance to delayed fracture.

[0021] This invention is based on the above insights. Specifically, the main structure of this invention is as follows.

[0022] [1] A clad steel sheet having a steel sheet and a coating formed on at least one side of the steel sheet, said steel sheet having, by mass%, C: 0.10% or more and 0.30% or less, Si: greater than 1.20% and 2.00% or less, Mn: 2.5% or more and 4.0% or less, P: 0.050% or less, S: 0.020% or less, Al: 0.10% or less, N: 0.01% or less, Ti: 0.100% or less, Nb: 0.002% or more and 0.050% or less, and B: 0.0008% or more and less than 0.0015%, satisfying the following formula (1), with the balance consisting of Fe and non- The composition of the material, which avoids impurities, is as follows: the combined area ratio of martensite and bainite is 95.0% or more; the area ratio of retained austenite is 4.8% or less; the area ratio of ferrite is 0.2% or more and 3.0% or less; the original austenite grain size is 10 μm or less; the boron concentration at the original austenite grain boundaries between adjacent martensite is 0.05% or more by mass; the deviation of the boron concentration at the original austenite grain boundaries between adjacent martensite within the same grain boundary is less than 0.010% by mass; and the deviation of the boron concentration at the original austenite grain boundaries between martensite and ferrite within the same grain boundary is 0.010% or more by mass.

[0023] ([%N] / 14) / ([%Ti] / 47.9)<1.0…Equation (1)

[0024] In formula (1), [%N] and [%Ti] represent the N and Ti content (mass %) in the steel, respectively.

[0025] [2] According to the galvanized steel sheet described in [1] above, as part of the above-mentioned composition, it further contains, by mass%, at least one of the following: V: 0.100% or less, Mo: 0.500% or less, Cr: 1.00% or less, Cu: 1.00% or less, Ni: 0.50% or less, Sb: 0.200% or less, Sn: 0.200% or less, Ta: 0.200% or less, W: 0.400% or less, Zr: 0.0200% or less, Ca: 0.0200% or less, Mg: 0.0200% or less, Co: 0.020% or less, REM: 0.0200% or less, Te: 0.020% or less, Hf: 0.10% or less, and Bi: 0.200% or less.

[0026] [3] A component made of a plated steel sheet as described in [1] or [2] above.

[0027] [4] A method for manufacturing a galvanized steel sheet, comprising:

[0028] The hot rolling process, wherein a steel billet having the composition described in [1] or [2] above is hot rolled to produce a hot rolled plate;

[0029] The pickling process involves pickling the aforementioned hot-rolled plate.

[0030] The cold rolling process involves cold rolling the hot-rolled sheet after the pickling process to produce a cold-rolled sheet.

[0031] The first annealing process involves heating the cold-rolled sheet to a first heating temperature above point Ac3.

[0032] In the cooling process, for the cold-rolled sheet after the first annealing process, cooling begins from the first heating temperature and is carried out at an average cooling rate of 50°C / s or more to a cooling stop temperature of 100°C or more and below Ms point.

[0033] The reheating process includes, after the cooling process, heating to a reheating temperature of 300°C or higher and 400°C or lower, maintaining at the reheating temperature for 60 seconds or higher, and then cooling to room temperature.

[0034] The cryogenic treatment process is performed after the reheating process;

[0035] The second annealing process, wherein, after the cryogenic treatment process, the steel sheet is heated to a second heating temperature above point Ac3 to obtain the steel sheet; and

[0036] The plating process involves plating the aforementioned steel plate to obtain a plating steel plate.

[0037] [5] The method for manufacturing coated steel sheet according to [4] above includes an alloying process for performing alloying treatment on the coated steel sheet after the above coating process.

[0038] [6] A method for manufacturing a component, comprising a step of forming a component by performing at least one of forming or joining processes on the plated steel sheet described in [1] or [2] above.

[0039] Invention Effects

[0040] According to the present invention, it is possible to provide plated steel sheets, components, and methods for manufacturing the same, having a tensile strength TS of 1180 MPa or higher, high strength, resistance to delayed fracture, and excellent plating properties. Detailed Implementation

[0041] The embodiments of the present invention will be described below. It should be noted that the present invention is not limited to the following embodiments.

[0042] The clad steel sheet of this embodiment has a steel sheet and a coating formed on at least one side of the steel sheet. The steel sheet contains, by mass%, C: 0.10% or more and 0.30% or less, Si: greater than 1.20% and 2.00% or less, Mn: 2.5% or more and 4.0% or less, P: 0.050% or less, S: 0.020% or less, Al: 0.10% or less, N: 0.01% or less, Ti: 0.100% or less, Nb: 0.002% or more and 0.050% or less, and B: 0.0008% or more and less than 0.0015%, satisfying the following formula (1), with the balance being Fe and unavoidable. The composition of the material is free of impurities, with the total area ratio of martensite and bainite being 95.0% or more, the area ratio of retained austenite being 4.8% or less, the area ratio of ferrite being 0.2% or more and 3.0% or less, the original austenite grain size being 10 μm or less, the boron concentration of the original austenite grain boundary between adjacent martensite being 0.05% or more by mass, the deviation of the boron concentration of the original austenite grain boundary between adjacent martensite within the same grain boundary being less than 0.010% by mass, and the deviation of the boron concentration of the original austenite grain boundary between martensite and ferrite within the same grain boundary being 0.010% or more by mass.

[0043] ([%N] / 14) / ([%Ti] / 47.9)<1.0…Equation (1)

[0044] In formula (1), [%N] and [%Ti] represent the N and Ti content (mass %) in the steel, respectively.

[0045] [Ingredients]

[0046] First, the appropriate range of the steel plate's composition and the rationale for defining it will be explained. It should be noted that, unless otherwise specified, in the following description, "%" indicating the content of the constituent elements in the steel plate refers to "mass %". Unless otherwise specified, "ppm" refers to "mass ppm". Furthermore, in this specification, the numerical range indicated by "~" refers to the range of values ​​before and after "~" as the lower and upper limits.

[0047] C: Above 0.10% and below 0.30%

[0048] Carbon (C) has the effect of strengthening martensitic and bainitic structures. When the C content is less than 0.10%, the area ratio of martensite and bainite decreases, and a tensile strength TS (hereinafter sometimes abbreviated as TS) of 1180 MPa or higher cannot be obtained. Therefore, the C content is set to 0.10% or higher. The C content is preferably set to 0.11% or higher.

[0049] On the other hand, when the C content is greater than 0.30%, carborides with B and iron are formed during annealing, which cannot cause a sufficient amount of B to segregate at the grain boundaries. Therefore, the C content is set to be below 0.30%.

[0050] The preferred C content is set to be below 0.28%.

[0051] Si: greater than 1.20% and less than 2.00%

[0052] Si is an effective element for solid solution strengthening. Furthermore, it has the effect of suppressing the precipitation of carborides, which degrades resistance to delayed fracture. Therefore, a Si content greater than 1.20% is required. Below 1.20%, carborides precipitate, the boron concentration at grain boundaries decreases, and resistance to delayed fracture decreases. Therefore, the Si content is set to be greater than 1.20%. Preferably, the Si content is set to 1.30% or higher.

[0053] On the other hand, Si is a ferrite stabilizing element that raises the phase transformation point. Therefore, when the Si content exceeds 2.00%, the annealing temperature becomes too high, making it impossible to achieve a pre-austenite grain size of less than 10 μm. Therefore, the Si content is set to 2.00% or less. Preferably, the Si content is set to 1.80% or less.

[0054] Mn: 2.5% or more and 4.0% or less

[0055] Mn is effective in improving hardenability. When the Mn content is less than 2.5%, the martensite and bainite area ratios decrease, leading to a decrease in strength. Therefore, the Mn content is set to 2.5% or higher. Preferably, the Mn content is set to 2.8% or higher.

[0056] On the other hand, when the Mn content is greater than 4.0%, the segregated areas become excessively hardened, reducing the resistance to delayed fracture. Therefore, the Mn content is set to 4.0% or less. Preferably, the Mn content is set to 3.5% or less.

[0057] P: below 0.050%

[0058] Phosphorus (P) segregates at the original austenite grain boundaries, reducing the resistance to delayed fracture. Therefore, the P content is set to 0.050% or less. The P content is preferably set to 0.025% or less. There is no specific lower limit for the P content; it can be 0%. However, reducing it to less than 0.001% would increase manufacturing costs, so it is preferably 0.001% or more.

[0059] S: below 0.020%

[0060] Segregation of sulfur (S) at the original austenite grain boundaries reduces the resistance to delayed fracture; therefore, the S content is set to 0.020% or less. Preferably, the S content is set to 0.018% or less. More preferably, the S content is 0.0040% or less, and even more preferably, 0.0020% or less.

[0061] There is no specific lower limit for the sulfur content, but since a content of less than 0.0001% would increase manufacturing costs, it is preferable to set it to 0.0001% or higher.

[0062] Al: below 0.10%

[0063] Al is an element that functions as a deoxidizing material, and to achieve this effect, the Al content is preferably set to 0.005% or more. On the other hand, when the Al content is greater than 0.10%, ferrite is easily formed, resulting in reduced strength. Therefore, the Al content is set to 0.10% or less. The Al content is preferably set to 0.05% or less.

[0064] N: below 0.01%

[0065] N forms nitrides with Nb and B, reducing the effectiveness of Nb and B addition. Therefore, the N content is set to 0.01% or less. The N content is preferably set to 0.006% or less. While no specific lower limit is set, from a manufacturing cost perspective, the N content is preferably set to 0.0001% or more.

[0066] Ti: below 0.100%

[0067] Ti has the effect of fixing N in steel as TiN, suppressing the formation of BN and NbN, thereby improving the effect of Nb and B addition and improving resistance to delayed fracture. To obtain these effects, the Ti content is preferably set to 0.005% or more. On the other hand, when the Ti content is greater than 0.100%, coarse Ti carbides are formed at the grain boundaries, which reduces the resistance to delayed fracture. Therefore, the Ti content is set to 0.100% or less. The Ti content is preferably set to 0.050% or less.

[0068] Nb: Above 0.002% and below 0.050%

[0069] Nb is dissolved or precipitated as fine carbides, inhibiting the growth of austenite grains during annealing. Furthermore, it can refine the grain size, thereby complicating the fracture path and improving resistance to delayed fracture. To achieve this effect, the Nb content is set to 0.002% or more. Preferably, the Nb content is set to 0.005% or more.

[0070] On the other hand, when the Nb content is greater than 0.050%, not only does the effect become saturated, but coarse Nb carbides also precipitate, reducing the resistance to delayed fracture. Therefore, the Nb content is set to 0.050% or less. Furthermore, the Nb content is preferably 0.040% or less.

[0071] B: Above 0.0008% and less than 0.0015%

[0072] Boron (B) has the effect of segregating at the original austenite grain boundaries, increasing grain boundary strength, and improving resistance to delayed fracture. To achieve this effect, the B content is set to 0.0008% or more. Preferably, the B content is set to 0.0009% or more.

[0073] On the other hand, when the boron content is 0.0015% or higher, it accumulates on the steel plate surface along with Si and Mn during annealing, forming oxides that reduce surface appearance and plating properties. Furthermore, the formation of borocarbides reduces resistance to delayed fracture. Therefore, the boron content is set to be less than 0.0015%. Preferably, the boron content is set to 0.0014% or less.

[0074] ([%N] / 14) / ([%Ti] / 47.9)<1.0…Equation (1)

[0075] To achieve the aforementioned effects of adding B and Nb, N, which readily combines with these elements, needs to be fixed with Ti. Therefore, the mole fraction of N is made less than the mole fraction of Ti. That is, the N and Ti content in the steel is adjusted to satisfy the above equation (1).

[0076] ([%N] / 14) / ([%Ti] / 47.9) is preferably 0.6 or less.

[0077] It should be noted that in formula (1), [%N] and [%Ti] represent the N and Ti content (mass %) in the steel, respectively.

[0078] The balance other than the above-mentioned components is Fe and unavoidable impurities. It should be noted that, regarding the optional components described later, if the content is below the lower limit, these optional elements are treated as unavoidable impurities since the effect of the present invention is not impaired.

[0079] [Optional Ingredients]

[0080] In addition to the above-mentioned composition, the coated steel sheet of this embodiment may also contain, by mass percent, at least one element selected from V: 0.100% or less, Mo: 0.500% or less, Cr: 1.00% or less, Cu: 1.00% or less, Ni: 0.50% or less, Sb: 0.200% or less, Sn: 0.200% or less, Ta: 0.200% or less, W: 0.400% or less, Zr: 0.0200% or less, Ca: 0.0200% or less, Mg: 0.0200% or less, Co: 0.020% or less, REM: 0.0200% or less, Te: 0.020% or less, Hf: 0.10% or less, and Bi: 0.200% or less.

[0081] V: Below 0.100%

[0082] V has the effect of forming fine carbides and improving strength. When the V content is greater than 0.100%, coarse V carbides sometimes precipitate, reducing the resistance to delayed fracture. Therefore, when V is present, the V content is set to 0.100% or less. The V content is preferably 0.080% or less, and more preferably 0.060% or less.

[0083] There is no particular limitation on the lower limit of the V content, which can be 0.000%, but since it has the effect of forming fine carbides and improving strength, it is preferably set to 0.001% or more. The V content is more preferably 0.005% or more, and even more preferably 0.010% or more.

[0084] Mo: 0.500% or less

[0085] Mo has the effect of improving hardenability and increasing the area ratio of bainite and martensite. The effect saturates when the Mo content is greater than 0.500%. Therefore, in cases where Mo is present, the Mo content is set to 0.500% or less. The Mo content is preferably 0.200% or less, and more preferably 0.150% or less.

[0086] There is no particular limitation on the lower limit of Mo content, which can be 0.000%, but since it has the effect of improving hardenability and increasing the area ratio of bainite and martensite, it is preferred to set it to 0.010% or more. More preferably, the Mo content is 0.020% or more, and even more preferably 0.030% or more.

[0087] Cr: less than 1.00%

[0088] Cr improves hardenability and increases the area ratio of bainite and martensite. The effect saturates when the Cr content exceeds 1.00%. Therefore, in cases where Cr is present, the Cr content is set to 1.00% or less. Preferably, the Cr content is 0.300% or less, more preferably 0.250% or less.

[0089] There is no particular limit to the lower limit of Cr content, which can be 0.000%, but since it has the effect of improving hardenability and increasing the area ratio of bainite and martensite, it is preferred to set it to 0.01% or more. More preferably, the Cr content is 0.015% or more, and even more preferably 0.030% or more.

[0090] Cu: below 1.00%

[0091] Cu has the effect of increasing strength through solid solution. In addition, Cu improves resistance to delayed fracture. When the Cu content is greater than 1.00%, grain boundary cracks are easily formed. Therefore, in cases containing Cu, the Cu content is set to 1.00% or less. The Cu content is preferably 0.60% or less, more preferably 0.30% or less.

[0092] There is no particular limitation on the lower limit of Cu content, which can be 0.00%, but since it has the effect of increasing strength through solid solution, it is preferably set to 0.01% or more. More preferably, the Cu content is 0.02% or more, and even more preferably 0.05% or more.

[0093] Ni: below 0.50%

[0094] Ni improves hardenability, but the effect saturates when the Ni content exceeds 0.50%. Therefore, in cases containing Ni, the Ni content is set to 0.50% or less. Preferably, the Ni content is 0.20% or less, and more preferably 0.15% or less.

[0095] There is no particular limitation on the lower limit of Ni content, which can be 0.00%, but since it has the effect of improving hardenability, it is preferably set to 0.01% or more. Ni content is more preferably 0.02% or more, and even more preferably 0.03% or more.

[0096] Sb: below 0.200%

[0097] Sb has the effect of inhibiting surface oxidation, nitriding, and decarburization of steel plates, but the effect saturates when the Sb content is greater than 0.200%. Therefore, in the case of Sb, the Sb content is set to 0.200% or less. The Sb content is preferably 0.050% or less, and more preferably 0.020% or less.

[0098] There is no particular limitation on the lower limit of Sb content, which can be 0.000%, but since it has the effect of inhibiting surface oxidation, nitriding and decarburization of steel plates, it is preferably set to 0.001% or more. More preferably, the Sb content is 0.002% or more, and even more preferably 0.005% or more.

[0099] Sn: below 0.200%

[0100] Like Sb, Sn also inhibits surface oxidation, nitriding, and decarburization of steel plates. The effect saturates when the Sn content exceeds 0.200%. Therefore, in cases containing Sn, the Sn content is set to 0.200% or less. Preferably, the Sn content is 0.050% or less, and more preferably 0.020% or less.

[0101] There is no particular limitation on the lower limit of the Sn content, which can be 0.000%, but since it has the effect of inhibiting surface oxidation, nitriding and decarburization of steel plates, it is preferred to set it to 0.001% or more. The Sn content is more preferably 0.002% or more, and even more preferably 0.005% or more.

[0102] Ta: Below 0.200%

[0103] Ta has the effect of forming fine carbides and increasing strength. When the Ta content is greater than 0.200%, coarse Ta carbides sometimes precipitate, reducing the resistance to delayed fracture. Therefore, when Ta is present, the Ta content is set to 0.200% or less. The Ta content is preferably 0.100% or less, and more preferably 0.070% or less.

[0104] There is no particular limitation on the lower limit of Ta content, which can be 0.000%, but since it has the effect of forming fine carbides and increasing strength, it is preferably set to 0.001% or more. Ta content is more preferably 0.005% or more, and even more preferably 0.010% or more.

[0105] W: Below 0.400%

[0106] W has the effect of forming fine carbides and improving strength. When the W content is greater than 0.400%, coarse W carbides sometimes precipitate, reducing the resistance to delayed fracture. Therefore, when W is present, the W content is set to 0.400% or less. The W content is preferably 0.300% or less, and more preferably 0.250% or less.

[0107] There is no particular limitation on the lower limit of W content, which can be 0.000%, but since it has the effect of forming fine carbides and improving strength, it is preferably set to 0.001% or more. More preferably, the W content is 0.005% or more, and even more preferably 0.010% or more.

[0108] Zr: below 0.0200%

[0109] Zr has the effect of spherizing inclusions and suppressing stress concentration, thereby improving toughness. When the Zr content is greater than 0.0200%, a large number of inclusions are sometimes formed, resulting in reduced toughness. Therefore, in the case of Zr content, the Zr content is set to 0.0200% or less. The Zr content is preferably 0.0150% or less, and more preferably 0.0100% or less.

[0110] There is no particular limitation on the lower limit of Zr content, which can be 0.0000%, but since it has the effect of making the inclusions spherical, suppressing stress concentration, and improving toughness, it is preferred to set it to 0.0001% or more. Zr content is more preferably 0.0010% or more, and even more preferably 0.0020% or more.

[0111] Ca: below 0.0200%

[0112] Ca can be used as a deoxidizing material. When the Ca content is greater than 0.0200%, a large number of Ca-based inclusions are sometimes formed, which reduces the resistance to delayed fracture. Therefore, when Ca is present, the Ca content is set to 0.0200% or less. The Ca content is preferably 0.0100% or less, and more preferably 0.0080% or less.

[0113] There is no particular limitation on the lower limit of Ca content, which can be 0.0000%, but since it can be used as a deoxidizing material, it is preferably set to 0.0001% or more. More preferably, the Ca content is 0.0005% or more, and even more preferably 0.0010% or more.

[0114] Mg: below 0.0200%

[0115] Mg can be used as a deoxidizing material. When the Mg content is greater than 0.0200%, a large number of Mg-based inclusions are sometimes formed, which reduces the resistance to delayed fracture. Therefore, when Mg is present, the Mg content is set to 0.0200% or less. The Mg content is preferably 0.0100% or less, and more preferably 0.0080% or less.

[0116] There is no particular limitation on the lower limit of Mg content, which can be 0.0000%, but since it can be used as a deoxidizing material, it is preferably set to 0.0001% or more. More preferably, the Mg content is 0.0005% or more, and even more preferably 0.0010% or more.

[0117] Co: below 0.020%

[0118] Co has the effect of increasing strength through solid solution strengthening. The effect saturates when the Co content exceeds 0.020%. Therefore, in the case of Co, the Co content is set to 0.020% or less. The Co content is preferably 0.015% or less, and more preferably 0.010% or less.

[0119] There is no particular limitation on the lower limit of the Co content, which can be 0.000%, but since it has the effect of improving strength through solid solution strengthening, it is preferably set to 0.001% or more. The Co content is more preferably 0.002% or more, and even more preferably 0.005% or more.

[0120] REM: below 0.0200%

[0121] REM has the effect of spherizing inclusions and suppressing stress concentration, thereby improving toughness. When the REM content is greater than 0.0200%, a large number of inclusions are sometimes formed, resulting in reduced toughness. Therefore, when REM is present, the REM content is set to 0.0200% or less. The REM content is preferably 0.0100% or less, and more preferably 0.0050% or less.

[0122] There is no particular limitation on the lower limit of REM content, which can be 0.0000%, but since it has the effect of making the inclusions spherical, suppressing stress concentration and improving toughness, it is preferred to set it to 0.0001% or more. REM content is more preferably 0.0005% or more, and even more preferably 0.0010% or more.

[0123] Here, REM refers to the lanthanides, namely scandium (Sc) with atomic number 21, yttrium (Y) with atomic number 39, and lanthanum (La) with atomic number 57 to lutetium (Lu) with atomic number 71. REM concentration refers to the total content of one or more elements selected from the above REMs. Preferably, REMs contain La, Ce, and Nd.

[0124] Te: below 0.020%

[0125] Te has the effect of spherizing inclusions and suppressing stress concentration, thereby improving toughness. When the Te content is greater than 0.020%, a large number of inclusions are sometimes formed, resulting in reduced toughness. Therefore, when Te is present, the Te content is set to 0.020% or less. The Te content is preferably 0.015% or less, and more preferably 0.010% or less.

[0126] There is no particular limitation on the lower limit of the Te content, which can be 0.000%, but since it has the effect of making the inclusions spherical, suppressing stress concentration, and improving toughness, it is preferably set to 0.001% or more. The Te content is more preferably 0.002% or more, and even more preferably 0.004% or more.

[0127] Hf: below 0.10%

[0128] Hf has the effect of spherizing inclusions and suppressing stress concentration, thereby improving toughness. When the Hf content is greater than 0.10%, a large number of inclusions are formed, and the toughness decreases. Therefore, when Hf is present, the Hf content is set to 0.10% or less. The Hf content is preferably 0.08% or less, and more preferably 0.05% or less.

[0129] There is no particular limit to the lower limit of Hf content, which can be 0.00%, but since it has the effect of making the inclusions spherical, suppressing stress concentration and improving toughness, it is preferred to set it to 0.01% or more.

[0130] Bi: below 0.200%

[0131] Bi has the effect of reducing segregation and improving flexibility. When the Bi content is greater than 0.200%, a large number of inclusions are sometimes formed, which reduces flexibility. Therefore, in the case of Bi content, the Bi content is set to 0.200% or less. The Bi content is preferably 0.100% or less, more preferably 0.050% or less. The Bi content is further preferably 0.010% or less, and even more preferably 0.005% or less.

[0132] There is no particular limitation on the lower limit of Bi content, which can be 0.000%, but since it has the effect of reducing segregation and improving flexibility, it is preferably set to 0.001% or more. More preferably, the Bi content is 0.002% or more, and even more preferably 0.003% or more.

[0133] [Steel Structure]

[0134] Next, the steel structure of the steel plate will be explained.

[0135] The combined area ratio of martensite and bainite is over 95.0%.

[0136] Both martensite and bainite are hard phases, and a total strength (TS) of 1180 MPa or higher is necessary. Therefore, the combined area fraction of martensite and bainite is set to 95.0% or higher. Preferably, the combined area fraction of martensite and bainite is 96.0% or higher. Since ferrite is formed from grain boundaries with uneven boron concentration, the upper limit for the combined area fraction of martensite and bainite is 99.8%.

[0137] Residual austenite area ratio: below 4.8%

[0138] The retained austenite may be included as a residual structure other than martensite and bainite. Therefore, the area fraction of retained austenite is set to 4.8% or less. More preferably, it is 4.7% or less, and even more preferably, it is 4.5% or less. Furthermore, it is preferable that the area fraction of retained austenite is 4% or less. More preferably, it is 3.8% or less, even more preferably, it is 3.7% or less, and even more preferably, it is 3.5% or less. The area fraction of retained austenite may be 0% or greater than 0%.

[0139] Ferrite area fraction greater than 0.2% and less than 3.0%

[0140] Ferrite forms from austenite grain boundaries where boron concentration is uneven. When the ferrite area fraction is 0.2% or more, the boron concentration at the original austenite grain boundaries where ferrite has not formed is sufficiently high, resulting in good resistance to delayed fracture. Therefore, the ferrite area fraction is set to 0.2% or more. Preferably, the ferrite area fraction is set to 0.3% or more, and more preferably to 0.5% or more.

[0141] On the other hand, the strength decreases when the ferrite area fraction exceeds 3.0%. Therefore, the ferrite area fraction is set to 3% or less. Preferably, the ferrite area fraction is set to 2.5% or less, and more preferably to 2.0% or less.

[0142] Here, the area ratios of each microstructure were determined as follows. Regarding the area ratio of retained austenite, in test pieces cut from each steel plate, the rolled surface was chemically ground to t / 4 of the plate thickness. The X-ray diffraction intensity and diffraction peak positions of the ground surface were measured using X-ray diffraction (XRD), and the volume fraction was calculated. This figure was taken as the area ratio of retained austenite. Next, the plate thickness section parallel to the rolling direction of each steel plate was ground and etched with a 3% (v / v) nitric acid ethanol solution. The t / 4 thickness position was used as the observation surface. Regarding the observation surface, SEM images of three fields of view were captured at 2000x magnification, with a field of view set to 57.1 μm × 42.9 μm. Based on the obtained SEM images, the total area ratio of martensite, bainite, and retained austenite, as well as the area ratio of the microstructure other than martensite, bainite, and retained austenite (ferrite), were determined through image analysis. The area ratios of martensite and bainite are calculated by subtracting the area ratio of retained austenite obtained by XRD from the area ratios of martensite, bainite, and retained austenite obtained by image analysis. The average of the three fields of view is taken as the area ratio of the microstructure.

[0143] Original austenite grain size: below 10 μm

[0144] By complicating the crack propagation path, resistance to delayed fracture can be improved. To achieve this effect, the original austenite grain size needs to be set to 10 μm or less. Therefore, the original austenite grain size is set to 10 μm or less. Preferably, the original austenite grain size is 9 μm or less. There is no particular limitation on the lower limit of the original austenite grain size, but from a production technology point of view, the original austenite grain size is preferably set to 1 μm or more. Furthermore, it is more preferable to set the original austenite grain size to 2 μm or more, and even more preferably to set it to 3 μm or more.

[0145] The grain size of the original austenite grains was determined as follows. After grinding the plate section parallel to the rolling direction of each steel plate, it was etched with picric acid aqueous solution to create an observation surface. In the observation surface, for the microstructure at the plate thickness t / 4 position, three SEM images were taken at 2000x magnification with a field of view set to 57.1 μm × 42.9 μm, obtaining SEM images. The grain size of the original austenite grains was determined from the obtained microstructure images through image analysis, and the average value of the three fields of view was taken as the grain size of the original austenite grains (average crystal grain size).

[0146] The boron concentration at the proto-austenite grain boundaries between adjacent martensite is ≥0.05% by mass.

[0147] Botanicals (B) segregate at the original austenite grain boundaries, strengthening the grain boundaries and improving resistance to delayed fracture. This effect is achieved when the B concentration at the original austenite grain boundaries is 0.05% or more by mass. Therefore, the B concentration at the original austenite grain boundaries (original austenite grain boundaries sandwiched between martensite structures) existing between adjacent martensite is set to 0.05% or more by mass. Preferably, the B concentration at the original austenite grain boundaries is 0.07% or more by mass, and more preferably 0.10% or more by mass.

[0148] There is no upper limit set for the boron concentration at the original austenite grain boundaries. However, in order to properly prevent the precipitation of hard boron carbides at the grain boundaries and further improve the resistance to delayed fracture, it is preferably less than 6%. More preferably, it is less than 2% by mass.

[0149] The deviation of boron concentration at the original austenite grain boundaries between adjacent martensite within the same grain boundary is less than 0.010% by mass.

[0150] To improve resistance to delayed fracture, in addition to the boron concentration at grain boundaries, it is also important that the boron concentration is uniform regardless of the grain boundaries. When the deviation is greater than 0.010%, a strength difference is generated within the grain boundaries, and cracking is prone to occur in areas where the boron concentration is locally less dense, thus diminishing the effect of improving delayed fracture resistance. Therefore, the deviation of boron concentration within the same grain boundary at the proto-austenite grain boundaries (proto-austenite grain boundaries sandwiched between martensite structures) between adjacent martensite is set to be less than 0.010% by mass. Preferably, the deviation is 0.009% or less by mass, more preferably 0.008% or less by mass.

[0151] Smaller deviations are preferred, but from a production technology perspective, the deviation can be set to 0.001% or higher. Furthermore, grain boundaries with martensite on both sides are beneficial for improving resistance to delayed fracture through B-segregation.

[0152] The deviation of boron concentration at the original austenite grain boundary between martensite and ferrite within the same grain boundary is greater than 0.010% by mass.

[0153] By forming grain boundaries between martensite and ferrite, the boron concentration of the proto-austenite grain boundaries sandwiched by martensite can be 0.05% by mass or more. Ferrite is not formed when the deviation of the boron concentration of the proto-austenite grain boundaries between martensite and ferrite within the same grain boundary is less than 0.010%. Therefore, the deviation of the boron concentration of the proto-austenite grain boundaries between martensite and ferrite (proto-austenite grain boundaries sandwiched by martensite and ferrite) within the same grain boundary is set to 0.010% by mass or more. Preferably, the deviation is 0.012% by mass or more, and more preferably 0.014% by mass or more.

[0154] There is no particular upper limit, but the deviation is preferably 0.200% or less in terms of mass%, and more preferably 0.100% or less in terms of mass%.

[0155] Here, the boron concentration and deviation of the proto-austenite grain boundaries were determined as follows. Needle-shaped samples were prepared from the region containing the proto-austenite grain boundaries using SEM-FIB (Focused Ion Beam). The obtained needle-shaped samples were analyzed using a 3DAP apparatus (LEAP4000XSi, manufactured by AMETEK). Measurements were performed in laser mode. The sample temperature was set below 80 K. The boron concentration of the proto-austenite grain boundaries was determined based on the number of boron ions and other ions detected from the proto-austenite grain boundaries. The boron concentration was set as the average of two samples. Additionally, five non-overlapping circular regions with diameters of 5 nm to 10 nm were defined on the surface of the measured proto-austenite grain boundaries. For each circle, a cylindrical volume extending along the normal direction of the grain boundary was defined, and the boron concentration on the grain boundary was determined for each cylinder. The standard deviation of this volume was taken as the deviation of the boron concentration.

[0156] It should be noted that in the above measurements, the original austenite grain size is very large relative to the area sampled by SEM-FIB method. Therefore, all grain boundaries of a sample are considered to be the same grain boundary. For example, the original austenite grain size is about 9 μm, while the area of ​​the sampled sample is about 0.1 μm in diameter. Therefore, the deviation in the obtained B concentration is a deviation within the same grain boundary.

[0157] Furthermore, the presence of austenite grain boundaries between martensite and ferrite can be confirmed by observing SEM images using the methods described above. Similarly, the presence of boundaries between adjacent martensite particles can also be confirmed by observing SEM images using the methods described above.

[0158] According to the present invention, it is possible to provide a coated steel sheet with a tensile strength of 1180 MPa or more. Preferably, the tensile strength of the coated steel sheet is 1250 MPa or more.

[0159] The aforementioned coated steel sheet has a coating formed on at least one side of the steel sheet. Preferably, the coating is a hot-dip galvanized layer, an alloyed hot-dip galvanized layer, or an electro-galvanized layer. The composition of the coating is not particularly limited and can be a known composition.

[0160] The composition of the hot-dip galvanized layer is not particularly limited and can be a general composition. In one example, the coating has the following composition: containing Fe: less than 20% by mass, Al: more than 0.001% by mass and less than 1.0% by mass, and also containing one or more of the following ingredients selected from the group consisting of Pb, Sb, Si, Sn, Mg, Mn, Ni, Cr, Co, Ca, Cu, Li, Ti, Be, Bi and REM, totaling more than 0% by mass and less than 3.5% by mass, with the balance consisting of Zn and unavoidable impurities.

[0161] In the case of a hot-dip galvanized coating, in one example the Fe content in the coating is less than 7% by mass; in the case of an alloyed hot-dip galvanized coating, in one example the Fe content in the coating is 7% by mass or more and 15% by mass or less, more preferably 8% by mass or more and 13% by mass or less.

[0162] There is no particular limitation on the amount of coating applied, but it is preferable to set the amount of coating applied per single side of the coated steel sheet to be 20-80 g / m². 2 In one example, the coating was formed on both the front and back sides of the steel sheet (high-strength cold-rolled steel sheet).

[0163] Next, the manufacturing method of galvanized steel sheet will be explained.

[0164] The method for manufacturing galvanized steel sheet according to this embodiment includes: a hot rolling process, wherein a steel billet having the above-mentioned composition is hot rolled to produce a hot-rolled sheet; a pickling process, wherein the hot-rolled sheet is pickled; a cold rolling process, wherein the hot-rolled sheet after the pickling process is cold-rolled to produce a cold-rolled sheet; a first annealing process, wherein the cold-rolled sheet is heated to a first heating temperature of Ac3 or higher; and a cooling process, wherein the cold-rolled sheet after the first annealing process is cooled from the first heating temperature at an average cooling rate of 50°C / s or higher. The process involves: cooling the steel sheet to a temperature above 100°C and below the cooling stop temperature (Ms point); a reheating process, wherein after the cooling process, the steel sheet is heated to a reheating temperature above 300°C and below 400°C, held at the reheating temperature for at least 60 seconds, and then cooled to room temperature; a cryogenic treatment process, wherein after the reheating process, cryogenic treatment is performed; a second annealing process, wherein after the cryogenic treatment process, the steel sheet is heated to a second heating temperature above the Ac3 point to obtain a steel sheet; and a plating process, wherein the steel sheet is plating treated to obtain a plated steel sheet.

[0165] First, a steel billet with the above-mentioned composition is manufactured.

[0166] Here, we will illustrate an example of the manufacturing conditions for steel billets before the hot rolling process.

[0167] First, the steel raw material is melted to produce molten steel with the above-mentioned composition. The melting method is not particularly limited; any known melting method such as converter melting or electric furnace melting is suitable. The resulting molten steel is solidified to produce a steel slab. The method for producing the steel slab from the molten steel is not particularly limited; continuous casting, ingot casting, or thin slab casting can be used. The steel slab can be hot-rolled after temporary cooling and reheating, or it can be continuously hot-rolled without cooling the cast steel slab to room temperature. Considering the rolling load and the formation of oxide scale, the steel slab heating temperature is preferably set to 1100°C or higher, and preferably 1300°C or lower. The steel slab heating method is not particularly limited; for example, it can be heated using a conventional furnace.

[0168] [Hot rolling process]

[0169] The steel billet is hot-rolled to produce a hot-rolled sheet. There are no particular restrictions on the hot rolling process; conventional methods can be used. Cooling after hot rolling is also not particularly restricted; the sheet is cooled to the coiling temperature. Next, the hot-rolled sheet is coiled into a coil. The coiling temperature is preferably set to 400°C or higher. This is because at coiling temperatures above 400°C, the strength of the hot-rolled sheet does not increase, making coiling easier. A more preferred coiling temperature is 550°C or higher. Furthermore, to appropriately prevent the formation of a thick oxide scale and further improve the yield, the coiling temperature is preferably set to 750°C or lower. It should be noted that the hot-rolled sheet may also be heat-treated before pickling for softening purposes.

[0170] [Pickling process]

[0171] After the hot rolling process, the hot-rolled plate is pickled in the pickling process.

[0172] The pickling process removes the oxide scale from hot-rolled sheets coiled into rolls. There are no particular limitations on the method for removing the oxide scale, but for complete removal, it is preferable to perform pickling simultaneously with uncoiling the hot-rolled coil. The pickling method is also not particularly limited and can be any conventional method.

[0173] [Cold rolling process]

[0174] After the pickling process, the hot-rolled sheet is cold-rolled in the cold rolling process to produce a cold-rolled sheet. For example, after removing the oxide scale, the hot-rolled sheet is properly cleaned and then cold-rolled to produce a cold-rolled sheet. There are no particular limitations on the cold rolling method; conventional methods are acceptable.

[0175] [First annealing process: heating to a temperature above point Ac3]

[0176] Next, in the first annealing process, the cold-rolled sheet is heated to a first heating temperature above Ac3 and annealed in the austenite single-phase region. If the first heating temperature is lower than Ac3, ferrite is formed. This ferrite has fewer dislocations during annealing, and during the second annealing, there are no dislocations that would become diffusion paths for boron (B), making it difficult for boron to segregate uniformly. Furthermore, if the temperature is excessively increased, the austenite grain size increases to greater than 10 μm. Therefore, the first heating temperature is set to above Ac3. The first heating temperature is preferably above Ac3 + 10°C, and more preferably above Ac3 + 15°C.

[0177] The austenite structure formed in the second annealing is the same crystal structure as that formed in the first annealing. Therefore, it is preferable to set the first heating temperature to 980°C or below so that the austenite grain size in the first annealing is also 10 μm or below. The first heating temperature is more preferably 950°C or below.

[0178] Point Ac3 is obtained using the following formula.

[0179] Ac3(℃)=881-206×[%C]+53×[%Si]-15×[%Mn]-27×[%Cu]-20×[%Ni]-1×[%Cr]+41×[%Mo]

[0180] (In the above formula, [%M] represents the content (mass%) of element M in the steel plate, and the value of elements that are not present is set to 0 (zero).)

[0181] [Cooling process: Starting from the initial heating temperature, cooling is carried out at an average cooling rate of 50℃ / s or higher until the cooling stop temperature is above 100℃ and below Ms point.]

[0182] [Reheating process: Heat to a reheating temperature of 300°C or higher but below 400°C, hold at the reheating temperature for at least 60 seconds, and then cool to room temperature]

[0183] After the first annealing process, in order to form a microstructure with retained austenite at the original austenite grain boundaries, the cold-rolled sheet undergoes a local quenching-distribution treatment during the cooling process. When the cooling stop temperature for local quenching is below 100°C, martensitic transformation occurs before carbon distribution, and a sufficient amount of retained austenite cannot be obtained before the second annealing. If the amount of retained austenite is insufficient, austenite with a different orientation than that formed in the first annealing is generated, making it difficult for boron (B) to segregate uniformly at the grain boundaries of such austenite. Therefore, the cooling stop temperature in the cooling process is set to 100°C or higher. The cooling stop temperature is preferably 120°C or higher, and more preferably 150°C or higher.

[0184] On the other hand, when the cooling stop temperature is above the Ms point, no martensitic phase transformation occurs, and therefore no carbon partitioning occurs during subsequent reheating, and no retained austenite is formed before the second annealing. If the amount of retained austenite is insufficient, austenite with a different orientation than that formed in the first annealing is formed, making it difficult for boron (B) to segregate uniformly at the grain boundaries of such austenite.

[0185] Therefore, the cooling stop temperature in the cooling process is set below the Ms point. The cooling stop temperature is preferably below Ms point -10°C, and more preferably below Ms point -20°C.

[0186] The Ms point is obtained using the following formula.

[0187] Ms(℃)=499-308×[C]-10.8×[Si]-32.4×[Mn]-16.2×[Ni]-27×[Cr]-10.8×[Mo]

[0188] (In the above formula, [M] represents the content (mass%) of element M in the steel plate, and the value of elements that are not present is set to 0 (zero).)

[0189] When the average cooling rate is less than 50°C / s, a ferrite phase transformation occurs. Since this ferrite contains almost no dislocations, the diffusion of boron during the second annealing process is slowed down by this ferrite phase transformation, resulting in insufficient enrichment of boron at grain boundaries in the final microstructure. Therefore, the average cooling rate is set to 50°C / s or more. Preferably, the average cooling rate is set to 60°C / s or more, and more preferably to 70°C / s or more.

[0190] There is no particular upper limit to the average cooling rate. If the cooling rate is too high, it will be difficult to control the first cooling stop temperature. Therefore, the average cooling rate is preferably set to 1000°C / s or less, and more preferably to 200°C / s or less.

[0191] It should be noted that the average cooling rate (°C / s) in the cooling process is “(first heating temperature (°C)) - (cooling stop temperature (°C)) / (cooling time (seconds) from the first heating temperature (°C) to the cooling stop temperature (°C))”.

[0192] When the reheating temperature is below 300℃, carbon partitioning is insufficient, and no retained austenite is formed before the second annealing. If the amount of retained austenite is insufficient, austenite with a different orientation than that formed in the first annealing is formed, making it difficult for boron (B) to segregate uniformly at the grain boundaries of such austenite.

[0193] Therefore, the reheating temperature is set to 300°C or higher. Preferably, the reheating temperature is 310°C or higher, and more preferably 320°C or higher.

[0194] On the other hand, when the reheating temperature exceeds 400°C, the untransformed austenite decomposes into cementite, and no retained austenite is formed before the second annealing. If the amount of retained austenite is insufficient, austenite with a different orientation than that formed in the first annealing is formed, making it difficult for boron (B) to segregate uniformly at the grain boundaries of such austenite. Therefore, the reheating temperature is set to 400°C or below. The reheating temperature is preferably 390°C or below, and more preferably 380°C or below.

[0195] Furthermore, if the holding time at the reheating temperature is less than 60 s, carbon distribution is insufficient, and no retained austenite is formed before the second annealing. If the amount of retained austenite is insufficient, austenite with a different orientation than that formed in the first annealing will be formed, making it difficult for boron (B) to segregate uniformly at the grain boundaries of such austenite.

[0196] Therefore, the holding time at the reheating temperature is set to 60 seconds or more. The holding time is preferably 80 seconds or more, and more preferably 100 seconds or more.

[0197] In addition, the holding time at the reheating temperature is preferably set to 900s or less, more preferably 600s or less.

[0198] After holding at the reheating temperature, cool to room temperature. Here, the room temperature, which is the cooling stop temperature in the reheating process, is not particularly limited and can be set to 5 to 50°C.

[0199] [Cryogenic treatment process]

[0200] Deep cryogenic treatment transforms the bulky retained austenite into carbon-enriched martensite. Nucleation of austenite with a different orientation than the first stage occurs from this newly obtained martensite, resulting in grain boundaries with uneven boron concentration. Film-like retained austenite also remains during this treatment, forming an austenite microstructure with the same crystal orientation as the first stage austenite during subsequent annealing, with boron enrichment and homogenization at its grain boundaries.

[0201] There are no particular limitations on the specific conditions for cryogenic treatment, but it is preferable to immerse the cold-rolled sheet after the reheating process in liquid nitrogen (-196°C) for at least 30 minutes. Furthermore, the immersion time of the cold-rolled sheet in liquid nitrogen is preferably set to 3 hours or less.

[0202] [Second annealing process: heating to a second heating temperature above point Ac3]

[0203] In the second annealing process, the steel sheet (cold-rolled sheet) obtained as described above is reheated to a second heating temperature above point Ac3 for annealing.

[0204] In this process, austenite with the same orientation as the austenite formed in the first annealing is generated using film-like retained austenite as a nucleus. During this formation, dissolved boron diffuses rapidly through dislocations in the martensite before the austenite phase transformation to the austenite grain boundaries, resulting in more uniform boron segregation. When the second heating temperature is below the Ac3 point, ferrite is formed, leading to a decrease in strength. Therefore, the second heating temperature is set to be above the Ac3 point. Preferably, the second heating temperature is Ac3 point +10°C or higher, and more preferably Ac3 point +15°C or higher.

[0205] On the other hand, if the temperature is excessively increased, the austenite grain size increases to more than 10 μm, and the delayed fracture characteristics decrease. Therefore, the second heating temperature is preferably set to 980°C or below. More preferably, the second heating temperature is 950°C or below.

[0206] [Platering process, alloying process]

[0207] Following the second annealing process described above, a plating process is performed, in which at least one side of the steel sheet is plated to obtain a plated steel sheet. After the plating process, the plated steel sheet (high-strength plated steel sheet) can be heat-treated in an alloying process to alloy the coating of the plated steel sheet, resulting in an alloyed plated steel sheet.

[0208] It should be noted that manufacturing conditions other than those mentioned above can be handled using conventional methods.

[0209] The thickness of the plated steel sheet obtained in this embodiment as described above is preferably set to 0.5 mm or more. Alternatively, the thickness is preferably set to 2.0 mm or less.

[0210] [member]

[0211] In this embodiment, at least a portion of the components can be made using the aforementioned clad steel sheet. In one example, the clad steel sheet can be formed into a target shape by stamping to manufacture an automotive part. It should be noted that the automotive part may include steel sheets other than the clad steel sheet of this embodiment as raw materials. According to this embodiment, a clad steel sheet with a TS of 1180 MPa or higher, possessing excellent resistance to delayed fracture and cladding properties, can be provided, thus enabling the provision of components with a TS of 1180 MPa or higher and possessing both excellent resistance to delayed fracture and cladding properties. The steel sheet of this embodiment is suitable for use as an automotive part that contributes to vehicle body weight reduction. The clad steel sheet of this embodiment can be appropriately used in automotive parts, especially in all components used as frame structural parts or reinforcing parts.

[0212] The manufacturing method of the above-mentioned component includes a process of forming the above-mentioned plated steel sheet and joining it to produce the component.

[0213] Forming processes can utilize general processing methods such as stamping without limitation. Furthermore, joining processes can utilize general welding methods such as spot welding and arc welding, as well as riveting and rivet joining without limitation.

[0214] Example

[0215] Steel with the composition shown in Table 1, with the balance consisting of Fe and unavoidable impurities, is smelted in a converter to produce steel billets. The obtained steel billets are then reheated and hot-rolled to obtain hot-rolled coils (hot-rolled sheets). Next, while uncoiling the hot-rolled coils, pickling is performed, followed by cold rolling to obtain cold-rolled sheets. The thickness of the hot-rolled sheets is set at 3.0 mm, and the thickness of the cold-rolled sheets is set at 1.2 mm. Annealing (first annealing step, cooling step, reheating step, cryogenic treatment step, second annealing step) is carried out using a continuous hot-dip galvanizing line under the conditions shown in Table 2 to obtain coated steel sheets (hot-dip galvanized steel sheet (GI), alloyed hot-dip galvanized steel sheet (GA)). The hot-dip galvanized steel sheets are immersed in a galvanizing bath at 460°C, with a coating density of 35 g / m² per side. 2 The coating adhesion amount. Alloyed hot-dip galvanized steel sheets are adjusted to 45g / m² per single side. 2 It is manufactured by alloying after the coating is applied and held at 520°C for 40 seconds.

[0216] It should be noted that, except for steel plate No. 6, deep cryogenic treatment is performed by immersing in liquid nitrogen (-196℃) for 60 minutes.

[0217]

[0218]

[0219] For the obtained steel plates, the following were evaluated using the method described above: the total area ratio of martensite and bainite, the area ratio of retained austenite, the area ratio of ferrite, the original austenite grain size, the boron concentration at the original austenite grain boundaries between adjacent martensite, and the deviation of the boron concentration at the original austenite grain boundaries within the same grain boundary (the deviation of the boron concentration at the original austenite grain boundaries between adjacent martensite and the deviation of the boron concentration at the original austenite grain boundaries between martensite and ferrite within the same grain boundary). Additionally, tensile strength and resistance to delayed fracture were evaluated using the method described later. The results are shown in Table 3.

[0220] [Tension Test]

[0221] For the obtained steel plate, tensile tests were performed according to JIS Z 2241 (2011). A JIS No. 5 tensile test piece was cut from the direction orthogonal to the rolling direction as the length direction, and the tensile strength (TS) was measured. A tensile strength TS of 1180 MPa or higher was considered good.

[0222] [Delayed Fracture Test]

[0223] The delayed fracture resistance of steel plates was evaluated as follows. A 30mm × 110mm test piece was cut from the steel plate, with the rolling direction as the length direction. A strain gauge was attached to the test piece, and a 90-degree V-bending process was performed with a radius of curvature of 7mmR (R / t = 5.0). The opposing plates were closed together to achieve a tensile stress of 1800MPa on the surface of the test piece, thus creating a test piece for evaluating delayed fracture resistance. This test piece was then immersed in a hydrochloric acid aqueous solution at pH 3, and the presence of cracks was investigated after 100 hours.

[0224] Steel plates that do not develop cracks after 100 hours are considered to have good delayed fracture resistance. In the table, steel plates that do not develop cracks after 100 hours are indicated as having "excellent" delayed fracture resistance, while steel plates that do not develop cracks are indicated as having "poor" delayed fracture resistance.

[0225] [Coating Performance Evaluation]

[0226] Regarding coating performance, for each coated steel sheet, visually inspect for any uncoated areas. A sheet with no uncoated areas is considered to have good coating performance. In the table, steel sheets judged to have good coating performance are labeled "Excellent," and steel sheets judged to have poor coating performance are labeled "Inferior."

[0227]

[0228] As shown in Table 3, in the example of the present invention, the tensile strength TS is 1180 MPa or higher, and the resistance to delayed fracture and plating properties are excellent. On the other hand, in the comparative example, one or more of the tensile strength TS, resistance to delayed fracture, and plating properties are poor.

[0229] Furthermore, it is understood that since the steel plate of the present invention has high strength, excellent resistance to delayed fracture, and plating properties, the components obtained by forming, joining, and further forming and joining processes using the steel plate of the present invention are also high in strength, have excellent resistance to delayed fracture, and have plating properties, just like the steel plate of the present invention.

Claims

1. A clad steel sheet having a steel sheet and a coating formed on at least one side of the steel sheet, In the steel plate It has the following composition by mass%: C: ≥0.10% and ≤0.30%, Si: ≥1.20% and ≤2.00%, Mn: ≥2.5% and ≤4.0%, P: ≤0.050%, S: ≤0.020%, Al: ≤0.10%, N: ≤0.01%, Ti: ≤0.100%, Nb: ≥0.002% and ≤0.050%, and B: ≥0.0008% and ≤0.0015%, satisfying the following formula (1), with the balance being Fe and unavoidable impurities. The combined area ratio of martensite and bainite is over 95.0%. The area fraction of retained austenite is below 4.8%. The ferrite area fraction is above 0.2% and below 3.0%. The original austenite grain size was less than 10 μm. The boron concentration at the original austenite grain boundaries between adjacent martensite is greater than 0.05% by mass. The B concentration at the original austenite grain boundaries between adjacent martensite is less than 0.010% by mass within the same grain boundary. The deviation of the boron concentration at the original austenite grain boundary between martensite and ferrite within the same grain boundary is greater than 0.010% by mass. ([%N] / 14) / ([%Ti] / 47.9)<1.0…Equation (1) In formula (1), [%N] and [%Ti] represent the N and Ti content (mass %) in the steel, respectively.

2. The galvanized steel sheet according to claim 1, wherein, As part of the composition, the material further comprises, by mass%, at least one selected from the following: V: 0.100% or less, Mo: 0.500% or less, Cr: 1.00% or less, Cu: 1.00% or less, Ni: 0.50% or less, Sb: 0.200% or less, Sn: 0.200% or less, Ta: 0.200% or less, W: 0.400% or less, Zr: 0.0200% or less, Ca: 0.0200% or less, Mg: 0.0200% or less, Co: 0.020% or less, REM: 0.0200% or less, Te: 0.020% or less, Hf: 0.10% or less, and Bi: 0.200% or less.

3. A component made using the plated steel sheet as described in claim 1 or 2.

4. A method for manufacturing a galvanized steel sheet, comprising: A hot rolling process, wherein a steel billet having the composition described in claim 1 or 2 is hot rolled to produce a hot-rolled plate; The pickling process, wherein the hot-rolled plate is pickled; The cold rolling process involves cold rolling the hot-rolled sheet after the pickling process to produce a cold-rolled sheet; The first annealing process involves heating the cold-rolled sheet to a first heating temperature above point Ac3. The cooling process, wherein, for the cold-rolled sheet after the first annealing process, cooling begins from the first heating temperature and is carried out at an average cooling rate of 50°C / s or more to a cooling stop temperature of 100°C or more and below Ms point; The reheating process includes, after the cooling process, heating to a reheating temperature of 300°C or higher and 400°C or lower, holding at the reheating temperature for 60 seconds or more, and then cooling to room temperature. The cryogenic treatment process is performed after the reheating process; The second annealing process, wherein, after the cryogenic treatment process, the steel sheet is heated to a second heating temperature above point Ac3 to obtain the steel sheet; and The plating process involves plating the steel plate to obtain a plated steel plate.

5. The method for manufacturing galvanized steel sheet according to claim 4, wherein, This includes an alloying process that performs alloying treatment on the plated steel sheet after the plating process.

6. A method for manufacturing a component, comprising the steps of forming a component by performing at least one of forming or joining processes on a plated steel sheet as described in claim 1 or 2.

Citation Information

Patent Citations

  • High strength cold rolled steel sheet excellent in workability and its production method

    JP2008106351A

  • High yield ratio and high strength steel sheet excellent in workability

    JP2013147736A